Effect of PBL hyperlink mind mapping, motivation, and parental involvement on physical education outcomes - Andri Yanto; Yendrizal Yendrizal; Damrah Damrah; Vega soniawan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aims to examine the effect of the Problem Based Learning (PBL) This study aims to examine the direct and indirect effects of the Problem-Based Learning model based on Mind Mapping Hyperlink media, learning motivation, and parental involvement on Physical Education (PJOK) learning outcomes. A quantitative approach with a path analysis design was employed. The sample consisted of 30 Grade X students of SMKN 2 Sungai Penuh using total sampling. Data were collected through Likert-scale questionnaires for PBL perception, learning motivation, and parental involvement, while learning outcomes were obtained from academic records. The results indicate that PBL has the strongest direct effect on learning outcomes (β = 0.425), followed by learning motivation (β = 0.318) and parental involvement (β = 0.267). Indirect effects through parental involvement were also found, strengthening the influence of PBL and motivation. The model explains 88.6% of the variance in learning outcomes. In conclusion, PBL supported by motivation and parental involvement contributes significantly to improving PJOK learning outcomes.